Examining The Role Of Ethical Leadership On Employee Work Ethic, Ocb And Performance In Marketing Departments Of Universities In West Java - Badawi, Badawi (Westscience Press, 2024)
Ethics is critical issue at work environment. Several previous studies depicted that with ethical leadership, a harmonious work environment can be formed and it leads to better performance. This study aims to analyze the relationship between ethical leadership on work ethic, OCB (Organization Citizenship Behaviour) and employee performance in the Marketing Department of Higher Education in West Java. The population in this study were employees in the Marketing Department of Higher Education in West Java Indonesia. This research is categorized as a quantitative study with primary data obtained through questionnaires distributed to 180 employees of the Marketing Department of Higher Education in West Java. The analysis in this study used the Structural Equation Modeling (SEM) method with SmartPLS software. The results of the analysis in this study state that ethical leadership influence positively on work ethic, on OCB, and on performance in the Marketing Department of Higher Education in West Java. This study also confirms the significant influence of work ethic and OCB on the teaching performance of the employees. From the results of the research, higher education managers can develop ethical leadership so that an ethical work environment expands, OCB practices increase, and the performance of Marketing Department employees improves.